Fractionation of aquatic humic substances and dynamic of chromium species in an aquatic body influenced by sugarcane cultivation - Tadini, Amanda M. [UNESP]; Moreira, Altair B. [UNESP]; Bisinoti, Márcia C. [UNESP] (Sociedade Brasileira de Química, 2014)
This study had as main objectiveto evaluate the influence of AHS obtained from an area under sugarcane cultivation on the dynamics of chromium species (Cr(III) and Cr(VI)). Was studied complexing capacity (CC) with the AHS of chromium species and these were characterized using UV/Vis spectrophotometry, molecular fluorescence, elemental analysis and infrared. AHS with and without fractionation showed a greater aromaticity degree and a predominance of humic acids, and the E4/E6 and E2/E4 ratios suggested aromatic rings and a greater contribution from plants, which indicates lignin structures. The highest CCs were observed for the AHS fractionated, being fraction with molecular-size < 10 kDa and 10-30 kDa showed the highest ability to complex Cr(III) and Cr(VI) ions, respectively. These results are corroborating with C/H/N and UV/Vis data, where we can conclude that the AHS without fractionation had the greatest aromaticity and a predominance of humic acids in their structure.

Este estudo teve como objetivo principal avaliar a influência das SHA obtidas a partir de uma área de cultivo de cana de açúcar sobre a influência das espécies de crômio (Cr(III) e Cr(VI)). Foi estudada a capacidade de complexação (CC) das SHA com as espécies de crômio e estas foram caracterizadas por espectrofotometria de UV/Vis, fluorescência molecular, análise elementar e infravermelho. SHA com e sem fracionamento apresentou maior grau de aromaticidade e predominância de ácidos húmicos, e as razões E4/E6 e E2/E4 sugerem a presença de anéis aromáticos e maior contribuição das plantas e lignina. As maiores CC foram observados para a SHA fracionadas, sendo as frações com tamanho molecular < 10 kDa e 10-30 kDa as que apresentaram as maiores capacidades para complexar os íons Cr(III) e Cr(VI), respectivamente. Estes resultados corroboram com os dados de C/H/N e UV/Vis, permitindo concluir que as SHA sem fracionamento têm em sua estrutura maior grupos aromáticos e uma predominância de ácidos húmicos.
Keywords: Aquatic humic substances; complexation; Characterization